Micro, Small and Medium Enterprises - As an Engine of Economic Growth - Kaur, Dr. Gursimran (The journal of contemporary issues in business and government, 2019)
Building a robust industrial sector is constantly at the top of policymakers' and government officials' minds. Industries not only produce commodities for domestic consumption and export, but they also play a critical role in providing jobs for the country's young. While large industries such as iron and steel, automobiles, and electronic items are discussed when discussing GDP and economic growth, there is a Small Industrial Sector that plays an important role in both product manufacturing and job creation but is hidden from view of economists and policymakers. This is the sector of Micro, Small, and Medium Enterprises. The MSME industry in India employs about 11 crore people and accounts for roughly 17 percent of the country's GDP. This industry is widely acknowledged as a significant contributor to GDP and a growth booster. The sector serves as an auxiliary unit to big firms, assisting them in meeting their business requirements and demands, so contributing to the country's socio-economic development and inclusive growth. The current study attempts to focus on the enormous growth potential/development prospects available in India while also examining the performance of MSMEs and the obstacles they encounter.